A Chinese patient with Toriello–Carey syndrome and an interstitial deletion of 3q. Issue 3 (17th October 2016) - Xie, Lulu; Luo, Xianqiong; Yang, Jie; Wang, Junping; Nie, Chuan; Wang, Zhu
Abstract : Toriello–Carey syndrome (T–CS), which was first described by Toriello and Carey, is a rare multiple congenital anomaly syndrome characterized by agenesis of the corpus callosum, Pierre Robin sequence, unusual facial appearance, and other anomalies. Tracheal or laryngeal anomalies are reported as a common manifestation of T–CS. These anomalies can lead to respiratory distress and respiratory tract infection. The cause of T–CS is unknown, although there have been reports of patients with a clinical diagnosis of T–CS and a chromosome anomaly. We describe another such patient who was found to have an interstitial deletion of 3q (3q12.1‐q21.3). © 2016 Wiley Periodicals, Inc.